2015
DOI: 10.1103/physrevlett.114.156803
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Damping of Collective Spin Modes in a Two-Dimensional Fermi Liquid with Spin-Orbit Coupling

Abstract: A Fermi liquid with spin-orbit coupling (SOC) is expected to support a new kind of collective modes: oscillations of magnetization in the absence of the magnetic field. We show that these modes are damped by the electron-electron interaction even in the limit of an infinitely long wavelength (q = 0). The linewidth of the collective mode is on the order of ∆2 /EF , where ∆ is a characteristic spin-orbit energy splitting and EF is the Fermi energy. Such damping is in a stark contrast to known damping mechanisms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Temperature dependence of (a) the intensity, (b) full width at half maximum (FWHM), and (c) peak center, of the chiral spin mode damping of chiral spin waves [21,45]. At higher temperatures, inelastic scattering mechanisms, e.g., electronelectron [45,66] or electron-phonon [67] interactions, may also contribute to damping.…”
Section: Fig S7mentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature dependence of (a) the intensity, (b) full width at half maximum (FWHM), and (c) peak center, of the chiral spin mode damping of chiral spin waves [21,45]. At higher temperatures, inelastic scattering mechanisms, e.g., electronelectron [45,66] or electron-phonon [67] interactions, may also contribute to damping.…”
Section: Fig S7mentioning
confidence: 99%
“…At higher temperatures, inelastic scattering mechanisms, e.g., electronelectron [45,66] or electron-phonon [67] interactions, may also contribute to damping. However, we found that a model, which incorporates the finite-temperature effects only via thermal smearing of the Fermi functions and neglects inelastic damping mechanisms, describes the experiment rather well.…”
Section: Fig S7mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 SO coupling was predicted to deeply modify the nature of these excitations, leading to chiral collective modes. [19][20][21] Conversely, it was shown that Coulomb interaction can induce a striking organization of the SO fields acting on a spin wave. [22][23][24][25] Indeed, for the two main kinds of collective spin modes of quantum wells (intra-and inter-subband), Coulomb interaction transforms the D'yakonov-Perel' decoherence scenario into a constructive scenario, where the spin dynamics is governed by a collective SO field B coll SO (q).…”
Section: Introductionmentioning
confidence: 99%
“…In a related study [85], the intrinsic linewidth of the chiral spin waves due to the interplay of SOC and momentum exchange between '+' and '−' spin populations (transversal SCD) was analyzed using diagrammatic expansion techniques. It was shown that, because of SOC, dissipation due to transverse SCD -usually vanishing as q → 0 -remains non-zero even at q = 0.…”
Section: Chiral Spin Wavesmentioning
confidence: 99%